Sand flies (Diptera, Psychodidae, Phlebotominae), vectors of Leishmania protozoa, at an Atlantic Forest Conservation Unit in the municipality of Nísia Floresta, Rio Grande do Norte state, Brazil. Issue 1 (December 2016) - Pinheiro, Marcos; Silva, Marcel; Júnior, João; da Silva, José; Alves, Maria; Ximenes, Maria
Abstract Background Sand flies are insect vectors of protozoa from the genusLeishmania, causative parasites of visceral and American tegumentary leishmaniases. The present study discusses the bioecological aspects of sand fly species, transmitters ofLeishmania protozoa, in different ecotopes of an Atlantic Forest Conservation Unit located in the metropolitan region of Natal, Rio Grande do Norte state, Brazil. Methods Two monthly captures were made in 1 year, using CDC light traps, in two anthropized and two preserved environments. Results A total of 2936 sand flies belonging to the following ten species were captured:Evandromyia walkeri, Evandromyia evandroi, Psychodopygus wellcomei, Sciopemyia sordellii, Psathyromyia brasiliensis, Lutzomyia longipalpis, Evandromyia lenti, Psathyromyia shannoni, Nyssomyia whitmani andNyssomyia intermedia . The most common species wasE. walkeri (77.6 %), followed byE. evandroi (17.5 %). Forest was the site with the greatest abundance (32.4 %), followed by bamboo grove (26.3 %). Conclusions Sand flies were generally more abundant in the rainy season andL. longipalpis, a vector species ofLeishmania infantum, was adapted to anthropized environments. It was confirmed thatP. wellcomei, a vector ofLeishmania braziliensis in Amazônia, is a species associated with more preserved environments, and occurs only in the rainy season.